Financing: From supporting agricultural production to transforming food systems - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2025)
Theory and practice around the financing of agricultural and food production have evolved over the last 50 years amid changes in the role of agriculture in supporting economic growth and rural development, as well as perceptions of the most critical food and nutrition problems facing low- and middle-income countries (LMICs). This chapter examines key financial challenges in LMIC agrifood systems and describes related policy research, as well as highlighting possible policy options to mobilize future financing for food systems transformation.